Diagnosis and Treatment of Infections in the Burn Patient - David G. Greenhalgh; John L. Kiley (MDPI AG, 2024)
Infection is very common in burn patients because they lose the primary barrier from microorganism invasion, the skin. While there are attempts to prevent infections, topical antimicrobials and systemic prophylaxis tend to lead to more resistant organisms. After the initial resuscitation, the most common cause of death is from sepsis and multiple organ dysfunction syndrome. The diagnosis is difficult in the burn population because the constant exposure from the open wound leads to an inflammatory response that leads to persistent hypermetabolism. This paper reviews the current understanding and treatment of infection and sepsis in burns.